Electro-optic analyzer of angular momentum hyperentanglement - Wu, Ziwen (Sci Rep, 2016)
Characterizing a high-dimensional entanglement is fundamental in quantum information applications. Here, we propose a theoretical scheme to analyze and characterize the angular momentum hyperentanglement that two photons are entangled simultaneously in spin and orbital angular momentum. Based on the electro-optic sampling with a proposed hyper-entanglement analyzer and the simple matrix operation using Cramer rule, our simulations show that it is possible to retrieve effectively both the information about the degree of polarization entanglement and the spiral spectrum of high-dimensional orbital angular momentum entanglement.